2011
DOI: 10.1002/csr.258
|View full text |Cite
|
Sign up to set email alerts
|

Role of Internalization Process in Defining the Relationship between ISO 14001 Certification and Corporate Environmental Performance

Abstract: The relationship between ISO 14001 certification and corporate environmental performance has become an important research topic in recent years. Based on the internalization process of ISO 14001 (the process that consolidates and embeds a firm's beliefs, attitudes, and values into its management and employees), this paper examines how internalization can impact on the corporate environmental performance. It is found that the internalization process of ISO 14001 serves an important role in mediating the relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
90
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(96 citation statements)
references
References 76 publications
1
90
0
Order By: Relevance
“…Existing literature on the topic maintains that substantive implementation of ISO 14001 is driven mainly by internal factors (Boiral 2011;Gavronski et al 2008;Guoyou et al 2012), whereas the importance of external factors remains inconclusive:…”
Section: Discussion and Research Implicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Existing literature on the topic maintains that substantive implementation of ISO 14001 is driven mainly by internal factors (Boiral 2011;Gavronski et al 2008;Guoyou et al 2012), whereas the importance of external factors remains inconclusive:…”
Section: Discussion and Research Implicationsmentioning
confidence: 99%
“…Studies focusing on external pressures have not clearly concluded whether these pressures induce firms to commit fully to the standard's requirements or not (Boiral 2007;Castka and Prajogo 2013). In contrast, scholars who focus on internal motivations seem to agree on their importance in driving substantive implementation of ISO 14001 (Heras- Guoyou et al 2012). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, similar to most research undertaken to date in the EMS field, this study has also been quantitative in nature and consequently been unable to delve deeper into the integration of the ISO standard in SMEs and potentially reflected only the dominant inhouse biases of the SME managers who have responded to the survey (Borial, 2007). Relatedly, the study neither lends itself to imputations on the motivations underlying the uptake of ISO 14001 certification among SMEs (Bansal and Roth, 2000) nor an assessment of the extent to which ISO 14001 certification has been internalised (Qi et al, 2012). As identified in a series of studies (e.g.…”
Section: Discussionmentioning
confidence: 95%
“…ISO 14001), 5 to ensure that their products met the standards of ecological management adopted in OECD countries. From 2000 onward, the number of ecological management certificates issued to Chinese companies grew sharply (Qi et al 2011(Qi et al , 2012 to bring China, by 2007, to the position of a world leader in ISO 14001 certificates. Since then the number of ISO 14001 certificates in China has continued to increase while slowing down or even dropping in many other countries, including the United States and Japan ( Figure 1; Shvarts and Gerasimchuk 2010;Shvarts, Bunina, and Knizhnikov 2015).…”
Section: China's Green Shift In Domestic Policiesmentioning
confidence: 99%